Betaine Regulates the Production of Reactive Oxygen Species Through Wnt10b Signaling in the Liver of Zebrafish - Li, Ao; Gu, Yaqi; Zhang, Xiuzhen; Yu, Hairui; Liu, Dongwu; Pang, Qiuxiang (Frontiers in Physiology, 2022)
When fish are under oxidative stress, levels of reactive oxygen species (ROS) are chronically elevated, which play a crucial role in fish innate immunity. In the present study, the mechanism by which betaine regulates ROS production via Wnt10b/β-catenin signaling was investigated in zebrafish liver. Our results showed that betaine enrichment of diet at 0.1, 0.2 and 0.4 g/kg induced Wnt10b and β-catenin gene expression, but suppressed GSK-3β expression in zebrafish liver. In addition, the content of superoxide anion (O2·-), hydrogen peroxide (H2O2) and hydroxyl radical (·OH) was decreased by all of the experimental betaine treatments. However, betaine enrichment of diet at 0.1, 0.2 and 0.4 g/kg enhanced gene expression and activity of superoxide dismutase (SOD), glutathione peroxidase (GSH-PX) and catalase (CAT) in zebrafish liver. In addition, Wnt10b RNA was further interfered in zebrafish, and the results of Wnt10b RNAi indicated that Wnt10b plays a key role in regulating ROS production and antioxidant enzyme activity. In conclusion, betaine can inhibit ROS production in zebrafish liver through the Wnt10b/β-catenin signaling pathway.